Levels of microbial diversity affect the stability and function of dark fermentation bioreactors - Navarro-Díaz, Marcelo; Aparicio-Trejo, Valeria; Valdez-Vazquez, Idania; Carrillo-Reyes, Julián; Avitia, Morena; Escalante, Ana E. (Frontiers in Industrial Microbiology, 2024)
Hydrogen-producing microbial communities have instability and yield issues likely caused by reduced diversity resulting from pretreatments of original anaerobic digestion communities. We used hydrogen-producing consortia to examine the complex effect of diversity and microbial interactions on function (biogas production and stability). We established two treatments with 12 replicates maintaining culture conditions for hydrogen production, i) using no pretreatment and ii) a heat-shock pretreatment for hydrogenogenic bacteria enrichment, resulting in high and low diversity communities. We characterized microbial community composition and function (biogas, volatiles fatty acids and invasion susceptibility). The two treatment replicates followed different assembly and functional paths (although replicates of each treatment converged into similar compositions and stable levels of biogas production). Importantly, although the heat-treated bioreactors showed a 91.5% increase in mean biogas production, the non-treated bioreactors showed less invasion susceptibility (where only one of the 6 bioreactors was successfully invaded in contrast to all the 6 heat-treated bioreactors). Additionally, we found that in non-treated bioreactors, biogas production was associated with species (i.e. Ethanoligenens harbinense and Enterococcus olivae) other than Clostridium which is the most studied hydrogen-producing bacterial group. In summary, our results indicate that the effect of diversity loss on stability is different depending on the component measured (i.e. taxonomic or functional stability and invasion susceptibility) and identified new bacterial groups associated with hydrogen production which might guide future research to improve design and control of microbial consortia in biotechnological environments.